2019
DOI: 10.3390/ijms21010241
|View full text |Cite
|
Sign up to set email alerts
|

ORESARA15 Acts Synergistically with ANGUSTIFOLIA3 and Separately from AINTEGUMENTA to Promote Cell Proliferation during Leaf Growth

Abstract: Developing leaves undergo sequential coordinated cell proliferation and cell expansion to determine their final size and shape. Although several important regulators of cell proliferation have been reported, the gene network regulating leaf developmental processes remains unclear. Previously, we showed that ORESARA15 (ORE15) positively regulates the rate and duration of cell proliferation by promoting the expression of direct targets, GROWTH-REGULATING FACTOR (GRF) transcription factors, during leaf growth. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…For example, 1-MCP treatment in pak-choy (lower shelf-life like kale and broccoli) delayed the senescence and yellow of leaves by maintaining the chloroplast integrity during the storage at 20 °C [ 28 ]. Additionally, high throughput studies have identified hundreds of potential SAGs, some of which have been further demonstrated to have roles in senescence using functional genomics and reverse genetics approaches [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, 1-MCP treatment in pak-choy (lower shelf-life like kale and broccoli) delayed the senescence and yellow of leaves by maintaining the chloroplast integrity during the storage at 20 °C [ 28 ]. Additionally, high throughput studies have identified hundreds of potential SAGs, some of which have been further demonstrated to have roles in senescence using functional genomics and reverse genetics approaches [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…ore15 mutants exhibited increased leaf longevity and delayed leaf yellowing as compared to wild type. ore15 mutants showed delayed leaf senescence in response to dark, salt or oxidative stresses [ 15 ]. Expression studies have revealed that ORE15 transcript levels were mostly concentrated in young leaves and at lower levels in ageing leaves [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…( Liu et al, 2020 ). AtPLATZ3 (ORESARA15) enhances leaf growth by promoting the rate and duration of cell proliferation in the early growth stages and suppresses leaf senescence in later stages ( Kim et al, 2018 ; Jun et al, 2020 ). AtPLATZ7 ( RITF1 , RGF1-INDUCIBLE TRANSCRIPTION FACTOR1) plays a central role in mediating RGF1 signaling, which controls root meristem size through ROS signaling ( Yamada et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The article by Jun et al [19] focuses on revealing the still unclear molecular basis of the regulatory gene networking during leaf development. The authors studied the spatiotemporal patterns of the ORESARA15 (ORE) expression.…”
mentioning
confidence: 99%